Diphtheria Toxin/Human B-Cell Activating Factor Fusion Protein Kills Human Acute Lymphoblastic Leukemia BALL-1 Cells: An Experimental Study - Gao, Xin-pu; Liu, Zheng-min; Jiao, Yu-lian; Cui, Bin; Zhu, Yue-ting; Zhang, Jie; Wang, Lai-cheng; Zhao, Yue-ran (Chinese Journal of Cancer Research; Vol 24, No 3 (September 01, 2012): Chinese Journal of Cancer Research, 2012)
Objective: This study aimed to express a fusion protein of diphtheria toxin and human B cell-activating factor (DT388sBAFF) in Escherichia coli (E. coli) and investigate its activity in human B-lineage acute lymphoblastic leukemia 1 cells (BALL-1). Methods: A fragment of DT388sBAFF fusion gene was separated from plasmid pUC57-DT388sBAFF digested with Nde I and Xho I, and inserted into the expression vector pcold II digested with the same enzymes. Recombinants were screened by the colony polymerase chain reaction (PCR) and restriction map. The recombinant expression vector was transformed into BL21 and its expression was induced by isopropyl β-D-1-thiogalactopyranoside (IPTG). The recombinant protein was identified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and Western blot, and then purified by Ni2+-NTA affinity chromatography. The expression level of B cell-activating factor receptor (BAFF-R) on BALL-1 cells was assessed by real-time PCR. The receptor binding capacity of recombinant protein was determined by cell fluorescent assay. The specific cytotoxicity of recombinant protein on BALL-1 cells was detected by 3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT) assay. Results: The expression level of recombinant protein was 50% of total bacterial proteins in E. coli, and the recombinant protein could bind to BAFF-R-positive BALL-1 cells and thereby produce a cytotoxic effect on the cells. Conclusion: The fusion protein expression vector DT388sBAFF was successfully constructed and the recombinant protein with selective cytotoxicity against BALL-1 cells was obtained, providing foundation for further study of the therapy of human B-lineage acute lymphoblastic leukemia.